Metode Role Playing Siswa Kelas X Pada Mata Pelajaran Virus - Ita Rosita; Indra Purnama (Indonesian Journal of Innovation Multidisipliner Research, 2023)
The aim of this research is to determine the improvement in learning outcomes of Fatahillah High School X-C students who are taught using the role playing method on Virus material. The form of research used is classroom action research. The Classroom Action Research (PTK) method used is applying the role playing method to improve student learning outcomes on Virus material. The data collection technique is in the form of test questions with 20 multiple choice questions and indirect observation in the form of student activity observation sheets. The research results showed that the average value of student learning outcomes in cycle I was 66,07 with a completion percentage of 46,87% and increased in cycle II to 80,15 with a completion percentage of 81.25%. The application of the role playing method in biology learning can increase the learning outcomes of class X SMAS Fatahillah students from cycle I to cycle II by 14,5 %.